Penggunaan Model PBL Untuk Meningkatkan Aktivitas Belajar Siswa Pada Pembelajaran Tematik Terpadu Sekolah Dasar - Devi, Meila Yufriana; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The research is underpinned by The fact that the field shows low student involvement in integrated thematic learning, due to the lack of a model used in integrated thematic learning. Research aims to increase the activity of Learning students using the model PBL. This type of research is class action research, implemented in the planning, implementation, observation and reflection phases. Qualitative and quantitativeresearch approaches. The research venue of Padang City Elementary School . The subject of his research was class IV students with a total of 23 students . The research Data is collected based on student activity instruments , learning execution plan, teacher aspect observation sheet and student aspect. The results showed, the use of the lbl model in integrated thematic learning can improve student learning activities ., as well as students can already work with members of the group, in the end it comes down to improved student learning skills in integrated thematic subjects. The results showed an increase in student learning activities in the 63% Kesiklus II cycle to 93%. Dconclude that the use of the PBL model is very effective to increase student learning Activities.